Design of Customer Satisfaction Application at BCA Kcp Rengasdengklok Using C.45 Algorithm Method - April Lia Hananto; Shofa Sofiah Hilabi; Detrie Noviani (Information System; Universitas Buana Perjuangan Karawang, 2022)
Bank BCA always improves service quality by the slogan